Zinc oxide nanoparticles based passive saturable absorber for pulse generation in fiber laser - Nurul Alina Afifi Norizan; Fauzan Ahmad; Muhammad Quisar Lokman; Sulaiman Wadi Harun (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
A stable passive Q-switched pulsed generation in Erbium doped fiber laser by Zinc Oxide nanoparticles embedded in polyvinyl alcohol (ZnONP-PVA)-based saturable absorber is demonstrated in this paper. The surface morphology and thickness profile of the fabricated film were observed using FESEM and 3D measuring laser microscope with the measured thickness of 12 μm. Meanwhile the its optical properties is characterized using Raman spectroscopy. The developed ZnONP-PVA film, has modulation depth of 7.8% and intensity saturation of 88.97 MW/cm2. The threshold input pump power to generate Q-switched pulse is at 45.4 mW and can be tuned until 92.4 mW before the pulse diminished. The operating wavelength of generated pulse is at 1535 nm with 3 dB bandwidth approximately of 2 nm with exclusion of parasitic continuous wave lasing. As the input pump power was tuned from threshold to maximum value, the recorded pulse train of repetition rate is tunable from 73.53 kHz to 103.10 kHz while the pulse width decreases from 6.8 μs to 4.8 μs. The calculated maximum output power and pulse energy at maximum input pump power was 5.14 mW and 49.85 nJ, respectively. The measured signal to noise ratio was 56 dB indicated that the generated pulse by ZnO NP based passive saturable absorber was stable.